ChemInform Abstract: Catalyst Free Michael Addition of 3‐Methyl‐2‐pyrazolin‐5‐one to β‐Nitrostyrenes "on Water": A Green Protocol for Facile Synthesis of 4‐(1‐Aryl‐2‐nitroethyl)‐3‐methyl‐1H‐pyrazol‐5‐ol. Issue 10 (11th March 2014) - Meshram, H. M.; Kumar, Nadigama Satish; Nanubolu, Jagadeesh Babu; Rao, L. Chandrasekhara; Rao, N. Nageswara
Abstract The reaction is conducted under environmentally benign conditions.